Trans Fatty Acids in the Hong Kong Food Supply - Stephen W. C. Chung; S. K. Tong; Violette F. P. Lin; Melva Y. Y. Chen; Janny K. M. Ma; Y. Xiao; Y. Y. Ho (Journal of Chemistry)
This study aimed to examine trans fatty acids (TFA) content of 142 individual food items, including bakery, fast food, and other fatty food that may contain high level of TFA. TFA was detected in all samples, except for four samples including one plain bread, one sponge cake, and two batter-made foods (egg roll and eggette) samples. For those found to contain detectable TFA, the content ranged up to 4.7 g/100 g of food or 17.3% of total lipids. On a per 100 grams of food basis, the highest mean TFA content among the 18 food subgroups was the doughnuts/French toast subgroup (0.95 g), followed by the other pastries subgroup (0.49 g) and the bread with filling/topping subgroup (0.44 g). Among the samples, the highest TFA content is from a doughnut (4.7 g/100 g), followed by two cream-filled bread with shredded coconut (1.8 and 1.4 g/100 g) and a sweetheart cake (1.7 g/100 g). Only consuming one whole piece of doughnut would have reached 100% of the maximum daily TFA intake as recommended by WHO based on a 2000 kcal diet. About 78% of samples had TFA ≤0.3 g/100 g food. For the majority of the food samples available in Hong Kong, if TFA was present, C18:1 trans would possibly be the predominant one.